Economic and Environmental Assessment of Hydrogen Production from Brazilian Energy Grid - José Carlos Curvelo Santana; Pedro Gerber Machado; Cláudio Augusto Oller do Nascimento; Celma de Oliveira Ribeiro (Energies, 2023)
The Brazilian energy grid is considered as one of the cleanest in the world, because it is composed of more than 80% of renewable energy sources. This work aimed to apply the levelized costs (LCOH) and environmental cost accounting techniques to demonstrate the feasibility of producing hydrogen (H2) by alkaline electrolysis powered by the Brazilian energy grid. A project of hydrogen production, with a lifetime of 20 years, had been evaluated by economical and sensitivity analysis. The production capacity (8.89 to 46.67 kg H2/h), production volume (25 to 100%), hydrogen sale price (1 to 5 USD/kg H2) and the MAR rate were varied. Results showed that at 2 USD/kg H2, all H2 production plant sizes are economically viable. On this condition, a payback of fewer than 4 years, an IRR greater than 31, a break-even point between 56 and 68% of the production volume and a ROI above 400% were found. The sensitivity analysis showed that the best economic condition was found at 35.56 kg H2/h of the plant size, which generated a net present value of USD 10.4 million. The cost of hydrogen varied between 1.26 and 1.64 USD/kg and a LCOH of 37.76 to 48.71 USD/MWh. LCA analysis showed that the hydrogen production project mitigated from 26 to 131 thousand tons of CO2, under the conditions studied.